2021
DOI: 10.1108/jes-09-2020-0479
|View full text |Cite
|
Sign up to set email alerts
|

Impact of general trust on bank risk-taking: the moderating effect of confidence in banks

Abstract: PurposeThis study examines the effect of general trust (GT) and confidence in banks (CIB) on bank risk-taking. Besides, it explores the moderating role of CIB on the relationship between GT and bank risk-taking.Design/methodology/approachSecondary data was obtained from the World Value Survey, World Bank and BankFocus from 2011 to 2018. Two-step system GMM estimator was used to examine the links between the GT and CIB with bank risk-taking in MENA region.FindingsResults indicated that both GT and CIB negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 74 publications
(110 reference statements)
0
13
0
Order By: Relevance
“…Chen et al (2017) found that Chinese firms in high trust regions were more likely to acquire bank credit than those in lower trust regions. Masoud and Albaity (2021) examined the link between the level of general trust and bank risk-taking. They found that general trust was negatively linked to bank risk-taking in developed and developing markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen et al (2017) found that Chinese firms in high trust regions were more likely to acquire bank credit than those in lower trust regions. Masoud and Albaity (2021) examined the link between the level of general trust and bank risk-taking. They found that general trust was negatively linked to bank risk-taking in developed and developing markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The MENA countries are known for their similar cultural values, ethnic identity, and social norms (Masoud and Albaity 2021;Ayadi et al 2015;Lassoued et al 2018Lassoued et al , 2016Pitlik and Rode 2017). Similarly, the MENA region has been classified as a collectivistic community based on group-oriented decision-making (Kabasakal and Bodur 2002;Pitlik and Rode 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the MENA region has been classified as a collectivistic community based on group-oriented decision-making (Kabasakal and Bodur 2002;Pitlik and Rode 2017). In addition, the MENA region has been ranked second, after the East Asia region, in terms of banking industry development (Masoud and Albaity 2021;Bourgain et al 2012;Anzoategui et al 2010). Lastly, the majority of MENA countries have been classified as oil-rich economies representing 65% of the world's oil reserve, which might suggest why the impact of the COVID-19 pandemic might be different than for other countries (Albaity et al 2020;Mertzanis et al 2019;Mohamed et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging economies have been the major receivers in terms of studies concerning banks performance in risk-taking and profitability and their determinants. Some of the notable studies on emerging economies are Masoud and Albaity (2021), Staehr and Uusküla (2020), De Moraes et al. (2020), Gulati et al.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging economies have been the major receivers in terms of studies concerning banks performance in risk-taking and profitability and their determinants. Some of the notable studies on emerging economies are Masoud and Albaity (2021), Staehr andUusk€ ula (2020), De Moraes et al (2020), Gulati et al (2019), Wu et al (2019), Chen et al (2017), Chen et al (2015) and Soedarmano et al (2013). One of the essential determinants of a bank default-risk is bank market competition.…”
Section: Introductionmentioning
confidence: 99%